The Impact of Cooperative Learning Strategies on Teacher Engagement in South African Intermediate Phase Mathematics Classrooms - Chiphambo, Shakespear Maliketi; Makhoba, Thami Isaac; Ngqunguza, Avela; Nqoma, Lungiswa; Agyeman, Nana Yaw B.; Mtsi, Nomxolisi (Journal of Innovation in Educational and Cultural Research, 2025)
This study examined the impact of cooperative learning strategies on teacher engagement in South African intermediate-phase mathematics classrooms. This study explored the relationship between implementing cooperative learning strategies and the engagement levels of intermediate-phase mathematics teachers in a selected education district of South Africa. Using Johnson and Johnson's social independence theory, a quantitative approach was employed, gathering data from 41 teachers through structured questionnaires. The results reveal that teaching styles significantly correlate with teacher confidence in implementing cooperative learning strategies. Similarly, cooperative learning activities promoting critical thinking and learner engagement correlate positively. Teacher confidence consistently exhibits moderate positive correlations with several variables, while the regular implementation of cooperative strategies correlates with more adaptive teaching approaches. The study highlights significant correlations between teaching style adaptation, teacher confidence, critical thinking, and learner engagement, emphasizing professional development, flexible teaching strategies, and institutional support to enhance cooperative learning implementation and its educational impact. This research advances cooperative learning by highlighting critical thinking, engagement, and adaptable teaching. It provides actionable insights for educators and policymakers, emphasizing professional development and holistic practices to enhance teaching and learning outcomes.